Confrontation of protest against male chauvinism in arundhati roy’s the god of small things - Singla, Sarla (International journal of linguistics, literature and culture, 2016)
Roy portrays women’s marathon struggle for seeking the sense of ‘identity’ in male dominated conservative framework breaking the age-old snackles and constraints and to assert her right to live her own way. Roy attacks the prevailing hypocrisy of the society which builds a great barrier between man and woman. The setup of the male dominated society is such that it has little or nothing to offer to the unfortunately forsaken women like Ammu's who are literally forsaken everywhere they go and the greatest pain of it all comes when they are inflicted by ones who are so called your ‘own people’.